PEMBERDAYAAN SISWA MELALUI PELATIHAN MENULIS CERPEN BERBASIS KEARIFAN LOKAL - Umbarasari, Thea; Puspasari, Fitri; Nurhuda, Zamzam; Aqilah Zahra, Hasna Salsabila (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This community service program (PKM) is motivated by the low interest and limited skills in writing short stories among students of SMAN 7 Kota Serang, particularly those in Grade XII. These issues are influenced by the lack of regular practice in creative writing, the limited variety of instructional methods, and the minimal use of local wisdom as a source of literary inspiration. In fact, short story writing not only functions as a medium for developing literacy skills but also serves as a means to preserve local culture and strengthen students’ character.The objective of this program is to empower students through training in short story writing based on local wisdom, enabling them to produce creative, contextual, and meaningful literary works. The methods employed include interactive lectures, group discussions, writing practice, individual mentoring, work appreciation sessions, anthology publication, and evaluation. This program is implemented using a participatory approach so that students are not merely recipients of material but active subjects involved throughout the entire training process.The expected outcomes of this activity include improved student skills in short story writing, increased interest and motivation to create literary works, and the production of short stories that highlight values of local wisdom. In addition, this program provides benefits for teachers and the school by offering innovative strategies for teaching writing and strengthening literacy culture. Furthermore, the program is expected to contribute to the preservation of local wisdom through the literary works produced by students.Keywords: student empowerment; short story writing; local wisdom; literacy; PKM.